A Flow-Injection Method for the Determination of the Total Iron with 3,4-Dihydroxypenylacetic Acid using a Specially Home-Designed Injection System - Najib, Fadhil M. (Sulaimani Journal for Pure and Applied Sciences, 1999)
A special injection system was designed in place of the ordinary commertial rotary injection valve usually used in flow-injection analysis (FIA). The system is a combination of two glass liquid distributing valves, a three-way and a four-way types. The two valves were connected together with PVC tubings of 1 mm. I.D. in such a way to produce an external loop having a volume of about 100 μL. The loop can be loaded with the desired solution without disturbing the flow in the rest of the manifold. The system was used successfully to determine total Iron in iron-containing drugs spectrophotometrically using 3,4-dihydroxyphenyl acetic acid (3,4- DHPAA) as reagent at 596nm. and a flow-rate of 0.05mL/min. The carrier rate of 1 mL/min. The calibration curve was linear between 0 - 8.3 ppm total Iron with a correlation coefficient r = 0.99996 confidence interval (y ± ts / √n) was 72.44 ± 0.6 at 95% confidence limit degree of freedom = 5. Analysis of Iron containing drugs after dissolution with 0.005M HCl or HNO3 gave errors not exceeding 5% represented by recovery tests of standard Iron solutions added to these samples. At least 20 samples could be determined per hour with coefficient of variation between 1.1 - 1.4%.